A New Newsvendor Policy Model for Supply Chains by Considering Disruption Risk and Special Order in Fuzzy Mode - Mohsenzadeh Ledari, Ashkan (International journal of industrial engineering and operational research, 2024)
In this paper we proposed newsvendor problem with two suppliers that first supplier channel is in priority and first supplier is replaced by second supplier. Both of supplier prone to disruption risk and we use second supplier when in first supplier disruption risk occurred. If in both supplier disruption risked occurred, we use first supplier and for difference between order and amount which response we use special order from production. Budget that is allocated for buying a product from a production, amount of product that a production of first channel can deliver to the retailer/wholesaler and percentage that is payable in case of disruption in first channel that are fuzzy numbers. For solving this model, we use Maple 16 software and did sensitivity analysis on probability of disruption risk in each channel.